The Stratigy Of Renewable Energies In Algeria In Order To Address Climate Change And Achieve The Sustainable Development The Realities And The Prospects - TASSADIT, BOUSBAINE (Recherches économiques et managériales; Vol. 15 (2014): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(JUIN), 2014)
The climate changes which the world confronts today constitute an important challenge because of the effects of global warning in different fields, moreover, the problem of misusing the natural resources and the decline of the environment have a big impact on weakness of economic development. These challenges have pushed the world countries to seek for alternative, and the renewable energies were the best solution which can provide energy to ensure the continuity of economic activity without harming the environment. In this case Algeria has pursued this international method toward keeping environment by adopting the necessary measures and elaborating the suitable strategy to get energy and achieve the sustainable development.        Key Words : renewable energy, sustainable development, natural resources, the strategy.      الملخص :     تشكل التغيرات المناخية التي يواجهها العالم اليوم تحديا مهما، نظرا لما صاحب ظاهرة الاحتباس الحراري من انعكاسات طالت  مختلف المجالات والأبعاد الإنسانية، كما أن مشكلة سوء استخدام الموارد الطبيعية وتدهور البيئة أصبحت لها أثرا واضح على إضعاف التنمية الاقتصادية. هذه التحديات وضعت دول العالم أمام واقع جديد يفرض عليها البحث عن البديل، فكانت الطاقات المتجددة الحل البديل   الذي يسمح بالحصول على الطاقة لضمان سيرورة النشاط الاقتصادي دون الإضرار بالبيئة. الجزائر وبدورها سلكت هذا النهج الدولي نحو الحفاظ على البيئة من خلال  الاعتماد على التدابير الضرورية ووضع الإستراتجية الملائمة  للحصول على الطاقة وتحقيق التنمية المستدامة. الكلمات الدالة: الطاقة المتجددة، التنمية المستدامة، الموارد الطبيعية،الإستراتجية.